Формальные методы анализа дискретных систем с использованием языка спецификаций - Крывый, С.Л.; Чугаенко, А.В. (Кибернетика и системный анализ, 2009)
Описано реалізацію алгоритму переведення набору діаграм MSC (документа MSC) в подійно еквівалентну йому мережу Петрі, наведено доказ коректності зазначеного алгоритму. Мережа, що отримана таким чином, може бути використана для аналізу властивостей вихідного документа MSC. Наведений алгоритм є складовою частиною системи аналізу та верифікації документів MSC. The paper describes the realization of the algorithm for translating an MSC diagram set (MSC document) to Petri net modulo event equivalence and proves the correctness of the algorithm. The net obtained by this method can be used to analyze the properties of the original MSC document. The algorithm is a part of a system of MSC document verification and analysis.